ANALISIS PENGARUH HARMONISA PADA TRANSFORMATOR DISTRIBUSI DI HARI KERJA DAN HARI LIBUR PADA GEDUNG PERKANTORAN - Hudaya, Chairul (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2021)
Harmonics are a phenomenon of voltage waveform deviationand currents that are transmitted and distributed from source to load in the formpure sinusoidal waves. This research aims to learn aboutthe influence of harmonics on distribution transformers in office buildings as wellcompare the effect on weekdays and holidays. From the measurement results inSudirman Central Business District is known that transformers 1 and 3 existharmonics with a current THD percentage of 25.27% and 22.32% on weekdays.While on holidays there is transformer 1 which has a percentage of THD current17.24% which exceeds the IEEE 519-1992 allowable limit of 15%.The dominant harmonics are the 3rd, 5th, and 7th harmonics. With a percentage of THDcurrents that exceed the standard limits will result in performance and even degradationdamage to electrical equipment or components. The results of the study show that at the momentsmall load (holidays) THD the resulting current is not too large due to the loadless use than during large loads (working days).